EFFECT OF IMPLEMENTATION OF MANAGEMENT INFORMATION SYSTEM ON THE COMMUNITY OF PUTAT LOR VILLAGE, GONDANGLEGI, MALANG REGENCY - Salsabil, Aqilah Shafa; Firmansyah, A Rifqi; Saputro, Moch Erwin; Fakhrulloh, Mohammad Yusuf; Hofiyah, Anis (PERCIPIENCE International Journal of Social, Administration, & Entrepreneurship, 2025)
The rapid advancement of technology has encouraged the implementation of digital systems within government institutions to create more effective, transparent, and efficient governance. One of the innovations supporting this goal is the development of website-based information systems, which serve as a step toward realizing good governance. However, observations indicate that many village governments in Indonesia still rely on traditional administrative methods, making adaptation to the current digital era challenging. This study employs literature research from various journals related to web-based information systems and aims to examine the impact and effectiveness of web-based public services in Putat Lor Village, Gondanglegi District, Malang Regency. The Putat Lor Village Government has developed a web-based public service system as an innovation initiated by the Population and Civil Registration Service to improve administrative performance and service delivery. The system simplifies community data management, allowing residents to access services without visiting the village office, thus saving time and effort. Despite these advantages, public understanding of this innovation remains limited, highlighting the need for further socialization and education efforts by the local government to ensure optimal utilization of the technology.